2019
DOI: 10.4049/jimmunol.1900070
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Infection Induces Viral and Cellular Defective Ribosomal Products Encoded by Alternative Reading Frames

Abstract: The importance of antiviral CD8+ T cell recognition of alternative reading frame (ARF)–derived peptides is uncertain. In this study, we describe an epitope (NS1-ARF21–8) present in a predicted 14-residue peptide encoded by the +1 register of NS1 mRNA in the influenza A virus (IAV). NS1-ARF21–8 elicits a robust, highly functional CD8+ T cell response in IAV-infected BALB/c mice. NS1-ARF21–8 is presented from unspliced NS mRNA, likely from downstream initiation on a Met residue that comprises the P1 position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…This increase in IFN-α expression was associated with increased numbers of pDCs, which in turn could contribute to the bystander activation of autoreactive T cells. More recently, it was reported that a highly functional CD8+ T cell response is elicited by alternative reading frame (ARF) epitopes encoded by NS1 mRNA of IAV, which might have important implications on IAV-induced autoimmunity [55].…”
Section: Viral Infections and Induction Of Autoimmunitymentioning
confidence: 99%
“…This increase in IFN-α expression was associated with increased numbers of pDCs, which in turn could contribute to the bystander activation of autoreactive T cells. More recently, it was reported that a highly functional CD8+ T cell response is elicited by alternative reading frame (ARF) epitopes encoded by NS1 mRNA of IAV, which might have important implications on IAV-induced autoimmunity [55].…”
Section: Viral Infections and Induction Of Autoimmunitymentioning
confidence: 99%
“…derived from canonical reading frames of coding sequences) and cryptic MAPs (i.e. derived from non-canonical reading frames and non-coding sequences) (35,36). A more practical implication of our work is the integration of both translational (codon arrangements) and post-translational events (e.g., MHC-binding affinity) in predictive algorithms to enhance the predictive modeling of the immunopeptidome for cancer immunotherapy and peptide-based vaccines, where discovery of suitable target antigens remains a formidable challenge (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not the virus makes direct use of uORF proteins, it is clear that the adaptive immune system can recognise epitopes from within their reading frames (Fig 3F). MHC I presentation of uORF-derived peptides poses the risk of an adaptive immune response developing against sNSVs, analogous to the risks posed to IAV by the presentation of alternative reading frames (ARFs) and defective ribosomal products (DRiPs) [6165]. Indeed, the risks posed by the presentation of uORFs are potentially even higher due to the high conservation of these sequences.…”
Section: Discussionmentioning
confidence: 99%